ChemInform Abstract: Supramolecular Architectures Incorporating Hydrogen‐Bonding Barbiturate Receptors. Issue 19 (May 2015) - Tron, Arnaud; Rocher, Mathias; Thornton, Peter J.; Tucker, James H. R.; McClenaghan, Nathan D.
Abstract Review: [53 refs.